Nahdlatul Ulama, the Fiqh Paradigm, and the Republic of Indonesia - Rochmat, Saefur (ASPENSI in Bandung, Indonesia, 2015)
ABSTRACT: The Republic of Indonesia was established based on a secular political system, but it did not follow the pure concept of the theory of secularisation. In the context of Indonesia nation-state, there were three competing major paradigms of the relationship between religion, especially Islam, and the state, that were: secular paradigm, Islamic ideological paradigm, and the âfiqhâ (Islamic study of laws) paradigm. In historical process, it was a result of compromise amongst the followers of secular and Islamic aspirations. In this âPancasilaâ (five basic principles of the Republic of Indonesia) state, Islam provides a moral basis for running the state. However, the proper role of religions should be negotiated amongst different political forces, such as was outlined in the seven words of the Jakarta Charter in 1945 and in the 1950s. In this regard, the traditionalist Muslims, especially the followers of Nahdlatul Ulama (NU), adopting the âfiqhâ paradigm, were able to develop a flexible standpoint in regard to the role of Islam in Indonesia compared to the modernist Muslims, who advocated an Islamic ideological paradigm. They (the traditionalist Muslims) were able to move from justifying the Republic of Indonesia to supporting an Islamic state and, then, again supporting the secular state. This was due to the âfiqhâ paradigm recognising the existing political system, while trying to improve it at the same time.KEY WORDS: Nahdlatul Ulama, Indonesia nation-state, the traditionalist Muslims, secular, Islamic ideological and âfiqhâ paradigms, and result of compromise.About the Author: Saefur Rochmat is a Lecturer at the Department of History Education, Faculty of Social Sciences UNY (State University of Yogyakarta), UNY Campus, Karangmalang, Yogyakarta, Indonesia. For acadeimic interests, the author is able to be contacted via e-mail at: rochmat@yahoo.comHow to cite this article? Rochmat, Saefur. (2015). âNahdlatul Ulama, the Fiqh Paradigm, and the Republic of Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.7(1) October, pp.45-62. Bandung, Indonesia: Minda Masagi Press, ISSN 2085-0980.Chronicle of the article: Accepted (June 17, 2015); Revised (August 17, 2015); and Published (October 28, 2015).